Electromagnetic analysis for complex satellite targets using time-frequency representations. Issue 1 (April 2021) - Sun, Xumin; Guan, Yongsheng
Abstract: An analytical method for electromagnetic scattering characteristics of complex satellite targets by using multilevel fast multipole algorithm (MLFMA) and short-time fourier transformation (STFT) is proposed in this paper. By constructing different electromagnetic models of satellite target with multi-scale structures and coatings, the aspect and polarization characteristics of radar cross section (RCS) and time-frequency representation (TFR) are studied. To validate the influence of the multi-scale structure and coating, the full-polarization RCS at specific angles, RCS statistical characteristics and TFR correlation are simulated and compared. It is concluded that the multi-scale structures and coating materials should be sufficiently considered to calculate the accurate scattering characteristics.